2012
DOI: 10.1143/jjap.51.11pj01
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Microplasma Application for Surface Modification of Biomaterials

Abstract: Atmospheric microplasma has been intensively studied for applications in various fields, since in this technology the generated field is only 1 kV (approx) under atmospheric pressure and a dielectric barrier discharge gap of 10 to 100 µm. A low discharge voltage atmospheric plasma process is an economical and effective solution for various applications such as indoor air control including sterilization, odor removal, and surface treatment, and would be suitable for medical applications in the field of plasma l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The gas, which enters through three inlet tubes just underneath the glass plate, flows through the porous glass into the plasma. For the last inlet system, the upper crucible and electrode have been replaced by a perforated stainless steel electrode covered with a ceramic coating, developed in previous work for microplasma–electrode applications . A single inlet feeds the gas top down into the system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gas, which enters through three inlet tubes just underneath the glass plate, flows through the porous glass into the plasma. For the last inlet system, the upper crucible and electrode have been replaced by a perforated stainless steel electrode covered with a ceramic coating, developed in previous work for microplasma–electrode applications . A single inlet feeds the gas top down into the system.…”
Section: Methodsmentioning
confidence: 99%
“…For the last inlet system, the upper crucible and electrode have been replaced by a perforated stainless steel electrode covered with a ceramic coating, developed in previous work for microplasma-electrode applications. [28][29][30][31] A single inlet feeds the gas top down into the system. The latter system has been tested both with and without a quartz wool filling in between the gas inlet and the perforated electrode.…”
Section: Inlet Set-upsmentioning
confidence: 99%
“…These studies have reported numerous applications, such as for sterilization [2,3], decomposition of harmful substances [4] and surface treatments [5][6][7]. In recent years, this area of research has been focused on the practical utilization of atmospheric plasma in the medical filed, such as for blood coagulation [8,9], wound healing [10][11][12] and cancer treatment [13][14][15].…”
Section: Introduction Of Atmospheric Plasma For Medical Applicationmentioning
confidence: 99%